Chronicles of the Costa Rican woman. Towards the bicentenary - Barahona Riera, Macarena (2021)
The chronicle of the women in their actions of a life rescued from other historical chronicles of the history of Costa Rican historiography, visualize names of indigenous legendary, Spanish women who came with their husbands and lost children and their lives on the routes of conquest and imperial domination, women of the Republic fighting in various ways in the war of the National Campaign , economically, politically, in education for girls and women, in the well-being of health and society, women who bequeathed to us their scientific, intellectual concerns, of women's rights in gender equality in a patriarchal society that was developing Republican citizens' rights slowly and faced with political military crises , coups, fractures of the coffee oligarchy and the constant demands of new social groups of proletarians, workers and women. This chronicle rescues, visualize the names of Costa Rican women, from indigenous originating, Spanish, Creoles, Afro-descendants and migrants. Chronicle of women's memories